2020
DOI: 10.2147/cmar.s289094
|View full text |Cite
|
Sign up to set email alerts
|

Independent Risk Factors of Early Recurrence After Curative Resection for Perihilar Cholangiocarcinoma: Adjuvant Chemotherapy May Be Beneficial in Early Recurrence Subgroup

Abstract: Purpose In current clinical practice, early recurrence (ER) is not commonly discussed in perihilar cholangiocarcinoma (pCCA), and its risk factors for this disease have not been well clarified. We carried out this study to analyze the risk factors contributing to ER and explored the prognostic factors after curative resection for pCCA. Patients and Methods A total of 335 consecutive pCCA patients were retrospectively analyzed. Risk factors contributing to ER were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A recent study suggested that poor pathological differentiation, perineural invasion, and high levels of preoperative CA19-9 were independent risk factors of ER. 5 All these studies included postoperative variables. Our research exploring preoperative factors found that high level of CEA and invasion of hepatic artery in images were associated with a higher likelihood of ER, whereas high level of blood glucose level and white blood cell count were associated with lower odds of ER independently.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study suggested that poor pathological differentiation, perineural invasion, and high levels of preoperative CA19-9 were independent risk factors of ER. 5 All these studies included postoperative variables. Our research exploring preoperative factors found that high level of CEA and invasion of hepatic artery in images were associated with a higher likelihood of ER, whereas high level of blood glucose level and white blood cell count were associated with lower odds of ER independently.…”
Section: Discussionmentioning
confidence: 99%
“…The ER of pCCA was defined as the occurrence of recurrence within 12 months after surgery based on previous studies. 5 So, individuals had recurrence within 12 months after surgery were enrolled to group ER, whereas those experienced tumor recurrence later or did not suffer from recurrence were classified into group non-ER. OS was defined as the interval between the date of operation and the date of last follow-up or death.…”
Section: Patient Cohort and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations